Production of Single Cell Protein from Banana Peel Waste in Batch Fermentation Using Saccharomyces Cerevisiae - Azwar, Azwar; Mukhlishien, Mukhlishien; Muslim, Abrar; Hadissa, Putri; Ningsih, Utari Hadi; Zanil, M. F.; Ali, J. M. (Jurnal Bahan Alam Terbarukan, 2021)
Through engineering the fermentation process, it is hoped that new data can be obtained that will explain the ability of Saccharomyces cerevisiae to maximize the production of single-cell protein (SCP). SCP microorganisms have a high protein content, making them suitable for use as a human protein source as well as food additives in the cattle and fishing industries. The goal of this experiment is to see if the microbe Saccharomyces cerevisiae can generate SCP from banana peel waste. Some of the process variables used in this study include the variation in nutrition, fermentation time, and the effect of pH variations on SCP production. Where the variation in pH used is 3; 3.5; 4; 4.5; 5; and 5.5. As for the nutrients used, namely (NH4)2SO4 and KH2PO4 with a variety of nutrients, namely 0; 0.3; 0.6; 0.9; and 1.2 grams. Then the fermentation time was varied to 1,2,3,4 days. This study also analyzed the growth of microorganism cells using wet weight and dry weight with variations in pH and nutrition. The variation in nutrition is the same as the variation in the previous analysis of protein content, and the fermentation time is 1,2,3,4,5,6, and 7. In the analysis of protein content with Kjeldahl protein, the obtained optimal pH is 4.5 and the optimal protein content is 0.6 grams. As for the fermentation time, the optimal protein content is obtained on the 4th day. For the growth of microorganisms, the optimal pH is obtained at a pH value of 4.5 with optimal nutrition of 0.6 grams, and the optimal fermentation time is obtained on the 7th day.